Clinical trials since 2020 of rapid anti-suicidal ideation effects of ketamine and its enantiomers: a systematic review - Sumra Sajid; J. John Mann; Michael F. Grunebaum (Translational Psychiatry, 2025)
Abstract Background Suicide is a global public health problem with few empirically supported treatments. Methods We conducted a systematic review of clinical trials (CT) since 2020 of racemic ketamine or one of its enantiomers’ (R/S) potential to reduce suicidal ideation or behavior (SIB). An initial PubMed search on April 15th, 2024 yielded 2483 results. 104 relevant CTs were identified. An additional search using other search engines on March 19th, 2024 yielded 52 sources. After screening, 14 RCTs met the inclusion criteria which required clinically significant SIB among participants, ketamine or one of its enantiomers as an anti-SIB treatment, and SIB as an outcome. We excluded neuroimaging studies, meta-analyses, reviews, and case reports. Open-label studies were also excluded except in the case of R-ketamine where we included 2 open trials due to limited published data for this enantiomer, yielding a total of 16 CTs. We used the Revised Cochrane risk-of-bias tool for the RCTs. CTs reviewed had suicidal ideation (SI) but none had suicidal behavior as an outcome. Results The studies include ketamine augmentation of other treatments such as electroconvulsive therapy (ECT), various routes of administration – intravenous (IV), intramuscular (IM), and intranasal (IN) – and single versus multiple dose designs. Multiple doses of IV ketamine/S-ketamine produced reductions in SI for periods of several days to weeks, while single doses showed shorter, more variable effects. Multiple and single doses of IN ketamine/S-ketamine and single doses of IV ketamine produced less consistent anti-SI results. IN and IV ketamine/S-ketamine administration appears to be well tolerated. R-ketamine appears to produce fewer side effects, but additional clinical research is needed to clarify its antidepressant and anti-SI effects in humans. Conclusion This review affirms the time-limited, anti-SI effects of ketamine and the need for personalized treatment. Limitations include study heterogeneity, small samples, and paucity of data for suicidal behavior or R-ketamine.